2018
DOI: 10.3389/fpsyg.2018.02531
|View full text |Cite
|
Sign up to set email alerts
|

The Adventures of Amaru: Integrating Learning Tasks Into a Digital Game for Teaching Children in Early Phases of Literacy

Abstract: In low-income countries, the history of academic failure is a liability for children acquiring literacy skills. It is thus important to develop strategies that motivate and focus these students on specific strategies to learn to read. Digital games can be useful in motivating students and assisting teachers in the teaching-learning process, but there are few interactive tools that effectively integrate tasks of direct instruction and good gameplay. This technical report describes an interactive digital game to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Of course this may change as technology evolves and learners adapt to the new technologies. Importantly, technology can be used as a beneficial tool in scaffolding the learning of struggling readers (de Souza et al, 2018;Lee, 2016Lee, , 2019O'Brien, Habib & Onnis, 2019).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Of course this may change as technology evolves and learners adapt to the new technologies. Importantly, technology can be used as a beneficial tool in scaffolding the learning of struggling readers (de Souza et al, 2018;Lee, 2016Lee, , 2019O'Brien, Habib & Onnis, 2019).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…As a means of scaffolding learning in the classroom, technological tools provide limitless practice [26][27][28] that can be individualized [24,29,30] to optimize for an individual reader's strengths and weaknesses. Additionally, modern computational tools utilizing speech recognition and synthesis application programming interfaces (APIs), allow for embedded tools to be provided in real-time for any given text.…”
Section: Introductionmentioning
confidence: 99%
“…Technology-based environments for instruction and intervention have some advantages over traditional methods, in that they are engaging, reduce social pressure to perform, are adaptable to individual performance with features like embedded scaffolding and feedback, as well as the crucial ingredient for struggling learners – extensive practice (Clark et al, 2016; Laurillard, 2016; de Souza et al, 2018). Nevertheless, meta-analytic findings report better student progress with teacher-based versus computer-based interventions (Dowker, 2005; Slavin et al, 2011), but these findings do not account for differences across computer-based programs, where some approaches may be more beneficial than others.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than being considered as a replacement for human-led instruction, it is suggested that technology-based approaches serve primarily as tools that can be used to remediate or optimize learning experiences for all individuals (Dowker, 2005; Rose and Strangman, 2007). Accordingly, it is recommended that technology-based instruction conforms to known learning and pedagogical principles (e.g., Butterworth and Yeo, 2004; Hirsh-Pasek et al, 2015); that is by “using the combination of images and sounds and through a paradigm that tries to understand human behavior and, as well, employ an approach that matches how effective teaching actually occurs” (de Souza et al, 2018, p. 7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation